Strategi Implementasi Pengarusutamaan Gender Bidang Pendidikan Islam - Ch, Mufidah (IAIN Ponorogo, 2011)
Islam encourages Moslems to seek for knowledge regardless the area boundary, age, and field of interest. However, the Islamic education in Indonesia has not been able to facilitate men and women to obtain equal education. This gender gap is found in the policy, management, and teaching institutions of Islamic education. This has an impact on learner output, his/her roles and responsibilities in society. Although the President Instruction No. 9/2000, which foreruns the implementation of gender mainstreaming in national development, has been implemented more than a decade, the policy is neither fully understood nor well implemented especially in the field of Islamic education. Gender mainstreaming is still questioned because a number of institutions and relevant parties have not shown serious responses yet to overcome gender gaps in such areas as policy making, management, and learning. Carrying out analytical study on the gender mainstreaming in Islamic education is, therefore, inevitable: i.e. whether or not it has been practiced based on the implementation guidelines of gender mainstreaming in the national development.